USE OF 3D-VISUALIZATION MEDIA IN NUCLEOPHILIC SUBSTITUTION REACTION MATERIAL TO IMPROVE STUDENTS' CONCEPT MASTERY - Dessi Nur Adiska; Liliasari Liliasari; Iqbal Musthapa (Jurnal Tadris Kimiya, 2020)
Development of technology is increasingly rapid today, including in the field of education. Technological developments are sometimes not used properly in the learning process, so that students not actively studying in class. The purpose of this study was to determine the effect of using 3D visualization media on nucleophilic substitution reaction material to improve students' concept mastery. Research method used was a quasi-experiment with pre-test and post-test design, involved 68 students from two different universities in West Java. The test instrument to measure concept mastery consisted of nine reasoned multiple-choice questions. The results showed that the use of 3D visualization media in nucleophilic substitution reaction materials can improve students' mastery of concepts. Based on the N-gain calculation results, University A was better than University B except for the indicators of determining that obtained a medium category and sorting that obtained a low category. There were four indicators of concept mastery used, including determining, analyzing, linking, and sorting indicators.